ANALYSIS OF THE INFLUENCE OF CRUDE OIL PRICES ON ECONOMY OF IRAQ - Hayder Saleh Aziz (Статистика и экономика, 2016)
In the article mechanisms of influence on economy of Iraq of the world oil prices are investigated; it is shown what consequences for the budget of Iraq can have reduction of prices of oil, and how it will be reflected in the country budget in the future and on the general stability in the state.